Analysis of Soil Permeability in Open Land in the UHAMKA East Jakarta Campus Environment as an Indicator of Water Absorption Capacity - Hoerudin; Rahma Aliya Sumediyana; Hanifa Safitri; Dede Padli; Dita Suci Dwiyanti; Intan Nia Saputri; Yesa Widiyanti; M.Addya Harielpaniadi; Laksanawati, Wahyu Dian (Universitas Mandiri, 2025)
This study aims to analyze the water absorption capacity of open land within the UHAMKA East Jakarta campus as an indicator of soil permeability. The methods used were the gravimetric method to measure soil water content and the infiltration method using a cylindrical tube to calculate the water infiltration rate. Samples were taken from three different locations, and the parameters observed included temperature, soil pH, post-oven humidity, and absorbed water volume. The results showed that each sample had varying physical and chemical characteristics. Samples with the highest humidity and lowest pH showed high permeability, while drier and neutral soils had lower permeability. This variation reflects differences in soil pore structure and organic content between locations. This study provides an initial overview of the potential of open land as a natural infiltration medium to support sustainable water management in urban campus environments.